2019
DOI: 10.1055/s-0039-1690718
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-Catalyzed Amination of α-Aryl Methyl Ethers

Abstract: α-Aryl amines are prevalent in pharmaceutically active compounds and natural products. Herein, we describe a Ni-catalyzed protocol for their synthesis from readily available α-aryl ethers. While α-aryl ethers have been used as electrophiles in Ni-catalyzed C–C bond formations, their use in C–heteroatom bond formation is much less prevalent. Preliminary mechanistic insight suggests that oxidative addition is facilitated by an anionic ligand and that reductive elimination is a reversible process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…The addition of formaldehyde to the reaction mixture led to the observation of des -cyano-MPMN/formaldehyde adduct 27 by GC–MS (Scheme , Hypothesis D). We have previously reported that α-CN anion 25 can be detrimental to catalysis. , Thus, we hypothesized that formaldehyde may be necessary to trap 25 and generate an innocuous metal alkoxide adduct to enable efficient catalysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of formaldehyde to the reaction mixture led to the observation of des -cyano-MPMN/formaldehyde adduct 27 by GC–MS (Scheme , Hypothesis D). We have previously reported that α-CN anion 25 can be detrimental to catalysis. , Thus, we hypothesized that formaldehyde may be necessary to trap 25 and generate an innocuous metal alkoxide adduct to enable efficient catalysis.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously reported that α-CN anion 25 can be detrimental to catalysis. 72,73 Thus, we hypothesized that formaldehyde may be necessary to trap 25 and generate an innocuous metal alkoxide adduct to enable efficient catalysis.…”
Section: ■ Introductionmentioning
confidence: 99%
“…10e Under these optimized conditions, we observed high yields and stereochemical fidelity across a range of pivalates (Scheme 2). Substrates with both electron-rich (4, 5) and electron-poor (7) aryl groups were tolerated. The electron-poor examples were particularly noteworthy, as they do not benefit from the lower dearomatization energies that electron-donating substituents can provide.…”
mentioning
confidence: 99%
“…Alcohols and their derivatives are attractive substrates because of the high incidence of C–O bonds and alcohols in natural products and pharmaceuticals as well as simple starting materials . Indeed, C­(sp 3 ) cross-coupling through C–O bond cleavage has been demonstrated to forge various bonds, including C–C, C–B, C–N, and C–P . Among these, stereospecific cross-couplings using enantioenriched alcohol derivatives offer a potentially powerful method for asymmetric synthesis because the alcohol precursors are easily accessible in high enantiopurity, the reactions often proceed with high stereochemical fidelity, and many of the products are otherwise challenging to synthesize asymmetrically …”
mentioning
confidence: 99%